Pengaruh Lingkungan Pengamatan pada Ketelitian Horisontal GNSS dengan Metode RTK-NTRIP - Syafril Ramadhon (Jurnal Nasional Pengelolaan Energi MigasZoom, 2020)
The aim of this research is to empirically prove the influence of the observation environment on the horizontal accuracy of GNSS by the RTK-NTRIP method with an emphasis on various possible obstruction conditions and the length of time to achieve accuracy ≤5 cm. The study was conducted by measuring the GNSS using the RTK-NTRIP method at locations that accommodate a variety of possible obstructions caused by the observation environment, namely: a location that is relatively obstruction-free, the location of the building in one of the four coordinate directions, the location of measurements in under the tree, and the measurement location between two buildings. Data analysis was performed descriptively by comparing horizontal accuracy which was able to be achieved at each location and time to achieve that accuracy. The results showed that obstruction at the observation environment is very influential on the length of time to reach accuracy ≤5 cm, even at the observation site between two buildings, accuracy ≤5cm cannot be achieved.